2015
DOI: 10.1021/acs.joc.5b01756
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a Dual Chemical and Physical Activation: Direct aza-Michael Addition of Anilines Promoted by Solvent Effect under High Pressure

Abstract: The unique combination of hexafluoroisopropanol (HFIP) employed as solvent and hyperbaric conditions (10-15 kbar) allows unprecedented 1,4-addition of poor nucleophiles, such as aromatic amines, onto sluggish (cumbersome) Michael acceptors without any promoter or workup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…However, the thermodynamic stabilization gained from formation of the intramolecular hydrogen bond shifts the equilibrium towards the Z-isomer over time. The equilibrium proportion of the E configuration in acetone-d 6 The reaction with 2a was performed using N-methylaniline, 1m to eliminate the intramolecular hydrogen bond and assess the resulting configurational and conformational effects. The reaction proceeded with equal efficacy to the activated anilines, and FTIR monitoring showed that the carbonyl stretch of enaminone 3m…”
Section: Resultsmentioning
confidence: 99%
“…However, the thermodynamic stabilization gained from formation of the intramolecular hydrogen bond shifts the equilibrium towards the Z-isomer over time. The equilibrium proportion of the E configuration in acetone-d 6 The reaction with 2a was performed using N-methylaniline, 1m to eliminate the intramolecular hydrogen bond and assess the resulting configurational and conformational effects. The reaction proceeded with equal efficacy to the activated anilines, and FTIR monitoring showed that the carbonyl stretch of enaminone 3m…”
Section: Resultsmentioning
confidence: 99%
“…The results are shown in Figure . In all cases, hexafluoroisopropyl esters of semistabilized allyl‐ and benzylsulfonates gave better yields than trifluoroethyl sulfonates . It is worth stressing that, under the same conditions with t BuOLi, nonstabilized hexafluoroisopropyl 1‐octanesulfonate 3c reacted poorly with benzaldehyde (giving 11 % of 6 ), and trifluoroethyl ester 3d was an optimal olefinating reagent (84 % yield of 6 ).…”
Section: Resultsmentioning
confidence: 93%
“…It is known that aprotic polar solvents favor the Michael reaction when charged nucleophiles are employed. 51 The use of THF, a solvent of lower polarity led to poor yield of 10b along with a complex mixture of products (entry 4). On the other hand, the use tetrabutylammonium fluoride trihydrate, as basic catalyst, produced 10b and 10c in similar yields to the previously obtained results (entries 5, 6).…”
Section: Scheme 2 Synthesis Of 15 From 14 Via Domino Reduction-lactammentioning
confidence: 99%